Rancang Bangun Web Responsif untuk Mendukung Petani Tanaman Hias: Studi Kasus Paguyuban Tanaman Hias Sekarsari dan Magersari - Kristiyanto, Daniel Yeri; Ananda, Ridho; Saintika, Yudha (LPPM UNIKA Santo Thomas Medan, 2023)
Marketing of ornamental plant products in Sekarsari and Magersari Farmers Association of Magelang still uses conventional methods. The conventional self-help management means that buying and selling activities are limited and have not optimally empowered the development of information technology. The adoption of Responsive Website technology is used to address the relevant issues through the implementation of information technology. Responsive Website is developed using the Scrum method and the Model View Controller (MVC) framework which is able to bridge one data with other data on an information system. The adoption of innovation forms an information system that is useful for transforming the sustainable marketing system and directing the governance of farmer groups to be effective and better. Responsive Web implementation is tested using Blackbox Testing. This responsive web enables the association to carry out substantial market expansion, facilitate remote interaction between customers and farmers, and attain rapid business growth.